MASALAH DISABILITAS DAN SOSIAL KEMASYARAKATAN: Laporan Hasil Penelitian Survey Kuantitatif bersama Pilar Analisa Indonesia - Subasno, Yohanes (Sekolah Tinggi Pastoral IPI Malang, 2017)
Researcher conducted a survey with Pilar Analisa Indonesia, intending to explore the opinion of the disabled and/or their parents about the problems faced by persons with disabilities from their own perspective in the realm of daily life. The study also explores the understanding of persons with disabilities of some important terms that become standard terminology in discussions of solving rehabilitation issues. This research was conducted in Malang Raya by using Primary Sampling Unit method (Multi-stage Random Sampling). Respondents engaged in research using interviews as a method of data collection were 318 persons. The survey illustrated that persons with disabilities see the four most important issues around their dwellings, i.e expensive cost of goods, difficulty finding employment, health problems and educational issues. Other problems are limitations of physical, communication difficulties, alienated, mental and physical limitations, lack of attention from the government and need of mentoring. The understanding of persons with disabilities to the term of “penyandang disabilitas” is 54.09%, the knowledge of the rights of persons with disabilities reaches 95.00%, the inclusion term is understood only by 16.25%. Persons with disabilities who do not understand law and regulation related to the protection and empowerment of persons with disabilities reached 95.42%.